Correction: Polysaccharides from Ulva prolifera O.F. Müller inhibit cell proliferation via activating MAPK signaling in A549 and H1650 cells. Issue 23 (7th November 2022) - Yang, Juan Juan; Wang, Ye Hua; Yin, Jiao; Leng, Hong; Shen, Song dong
Abstract : Correction for 'Polysaccharides from Ulva prolifera O.F. Müller inhibit cell proliferation via activating MAPK signaling in A549 and H1650 cells' by Juan Juan Yang et al., Food Funct., 2021, 12, 6915–6924, ; https://doi.org/10.1039/D1FO00294E .